2015
DOI: 10.1159/000430261
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism Between Saturated and Unsaturated Fatty Acids in ROS Mediated Lipotoxicity in Rat Insulin-Producing Cells

Abstract: Background/Aims: Elevated levels of non-esterified fatty acids (NEFAs) are under suspicion to mediate β-cell dysfunction and β-cell loss in type 2 diabetes, a phenomenon known as lipotoxicity. Whereas saturated fatty acids show a strong cytotoxic effect upon insulin-producing cells, unsaturated fatty acids are not toxic and can even prevent toxicity. Experimental evidence suggests that oxidative stress mediates lipotoxicity and there is evidence that the subcellular site of ROS formation is the peroxisome. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 58 publications
(69 reference statements)
4
68
0
Order By: Relevance
“…The dysfunction of pancreatic islet possibly results from downregulation of sterol regulatory element-binding protein (SREBP)-1c-mediated IRS-2/Akt pathway [44]. Palmitate also impairs glucose-stimulated insulin secretion and β-cell function in rat insulin-secreting INS-1 cells [46] and induces H 2 O 2 formation in the peroxisomes of RINm5F insulin-producing cells [47], showing its lipotoxicity in vitro. Furthermore, palmitate exposure may induce apoptosis in isolated islets from humans [43,48], possibly through its receptor cell death-inducing DFF45-like effector b (Cideb) [48].…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…The dysfunction of pancreatic islet possibly results from downregulation of sterol regulatory element-binding protein (SREBP)-1c-mediated IRS-2/Akt pathway [44]. Palmitate also impairs glucose-stimulated insulin secretion and β-cell function in rat insulin-secreting INS-1 cells [46] and induces H 2 O 2 formation in the peroxisomes of RINm5F insulin-producing cells [47], showing its lipotoxicity in vitro. Furthermore, palmitate exposure may induce apoptosis in isolated islets from humans [43,48], possibly through its receptor cell death-inducing DFF45-like effector b (Cideb) [48].…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…It was noted that an increase in intake of plant sources of fats and proteins in the diet would reduce the risk of CAD and DM type 2 (8). Several studies demonstrated that increased intake of mono- and poly-unsaturated fatty acids (MUFAs and PUFAs) and lower intake of saturated and trans-fatty acids are associated with a lower risk of DM type 2 (9-11). …”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of the proapoptotic action of PA is still poorly understood. Participation of caspases in PA‐induced apoptosis has been reported . Increase in the ROS is the important trigger in this process but also appears to be cell‐type dependent.…”
Section: Discussionmentioning
confidence: 97%